SCORING RUBRIC AS THE AUTHENTIC ASSESSMENT USING BY THE ENGLISH TEACHERS TO RUN THE NATIONAL CURRICULUM IN SOUTH SUMATERA, INDONESIA - Elsina Sihombing (English Language Teaching and Research, 2017)
One main point on K-13 curriculum that makes it differs from others is its measurement standard, using authentic assessment. Authentic assessment recommends Contextual Teaching and Learning (CTL) as one of the methods of learning at schools. The result of her research is remaining that authentic assessment indicates the measurement of the learners learning with the competence based in doing something related to the themes they learned. The power of competence is not on the knowledge they have mastered but on the learners’ ability to present along the process, demonstrate, or doing something instead, as the result of the knowledge essence they have, meaningful and is needed around the environment. Language authentic assessment emphasizing on the language production ability more than theory only (linguistics competence) in daily communication to meet various needs of the students. Since most of the teachers especially in Lubuklinggau South Sumatera are still unfamiliar with authentic assessment, therefore, it is important to familiarize them. Since there are many teachers who do not understand, do not know what to score up from the students learning in authentic assessment, the researcher thinks that it is important to release such a vagueness and un-certainty because it is also one of the ways of how to save Indonesia Education heading toward the upgraded and the best education. To do that, the researcher presents a contribution bridging them and the Government, as well, by producing a guide-book of authentic assessment focusing on scoring rubric, as the product of the this research.Keywords :  Scoring rubric, Authentic Assessment, National curriculum